Body and Gender, Soul and Reason in Late Antiquity - Clark, Gillian (E. Gillian) (Farnham Ashgate, 2011)
What does it mean to say that a human being is body and soul, and how does each affect the other? Late antique philosophers asked these central questions. The papers collected here explore their answers, and use those answers to ask further questions. -- preface
[Part 1]. Bodies and minds: the limits of reason: The Fathers and the children -- Cosmic sympathies: nature as the expression of divine purpose -- The Fathers and the animals: the rule of reason? -- Animal passions. [Part 2]. Bodies and gender: Christian challenges: Women and asceticism in late antiquity: the refusal of status and gender -- 'The bright frontier of friendship': Augustine and the Christian body as frontier -- Adam's womb (Augustine, Confessions 13.28) and the salty sea -- Bodies and blood: late antique debate on martyrdom, virginity and resurrection -- The old Adam: the Fathers and the unmaking of masculinity -- Adam's engendering: Augustine on gender and creation -- 'In the foreskin of your flesh': the pure male body in late antiquity. [Part 3]. Bodies and souls: the philosophic life. Victricius of Rouen: Praising the Saints -- Translating relics: Victricius of Rouen and fourth-century debate -- Translate into Greek: Porphyry of Tyre on the new barbarians -- Philosophic Lives and the philosophic life: Porphyry and Iamblichus -- Fattening the soul: Christian asceticism and Porphyry On Abstinence -- The health of the spiritual athlete -- Do try this at home: the domestic philosopher in late antiquity.
Keywords: Augustine, -- Saint, Bishop of Hippo -- Criticism and interpretation; Porphyry, -- approximately 234-approximately 305 -- Criticism and interpretation; Victricius, -- Saint, -- approximately 330-approximately 409 -- Criticism and interpretation; Mind and body -- History; Philosophy, Ancient; Sex role -- Religious aspects&delete& -- Christianity; Soul -- Christianity; Theological anthropology -- Christianity